Digital Democracy: Disparity Between Urban- Rural Digital Democracy in North Banten and South Banten, Indonesia - Bayu Nurrohman; Gilang Ramadhan; Luki Oka Prastio (Dealings Foundation Institute, 2026)
Digital platforms have now become a new avenue for citizens to express their opinions, hold those in power accountable, and engage in the political process. While it offers many benefits, digital democracy also faces significant challenges, including the digital divide. This research attempts to examine the disparity between urban and rural digital democracy in Banten Province, represented by North Banten and South Banten. The purpose of this research is to examine and understand the practice of digital democracy and its gaps in Banten Province. This research is urgently needed to examine how digital democracy is implemented in public spaces to encourage their participation in politics and government. The research is focused on Banten Province, as a significant gap in the implementation of digital democracy exists between urban areas (North Banten) and rural areas (South Banten). The research employed a qualitative method with a case study approach. The research findings indicate that the digital democracy gap between rural areas, represented by Lebak Regency and Pandeglang Regency, and the government in urban areas, represented by Tangerang City, Tangerang Regency, and South Tangerang City, is indeed present. The main gap is evident in the number of public spaces provided by the government for the public to participate in conveying aspirations, complaints, grievances, and even suggestions regarding the provision of public services. The gap also exists in the access that local communities have to the provided public spaces. Financial limitations affect the region's capacity to offer a more sufficient digital public space system.